Consumer Awareness of Food Waste Reduction - A Systematic Literature Review Following The Prisma Statement - Nefovski, Sasho; Petkovska mirchevska, Tatjana; Brzovska, Ezheni (My University, 2024)
This paper examines the role of social marketing in reducing food waste, focusing on consumer behaviour and awareness of its harmful effects. A systematic literature review (SLR) evaluates studies analysing marketing campaigns' relationship with food waste reduction. Increasing awareness and changing behaviour through marketing campaigns can significantly reduce food waste. This paper analyses relevant literature to present key findings and recommendations for effectively targeting consumers with communication strategies to reduce food waste. In addition, it explores recommendations for implementing point-of-sale activities and direct communication with consumers to promote sustainable food systems.